Evaluating the relationship between standing height, body mass index, body fat percentage with risk of inguinal hernia: a Mendelian randomization study - Yuting Li; Baihui Li; Fanlei Meng (Scientific Reports, 2024)
Abstract Observational studies have suggested links between standing height, BMI, body fat percentage, and inguinal hernia risk, but with inconsistent results. We conducted Mendelian randomization (MR) method to investigate their causal relationships. Independent SNPs associated with standing height, BMI, and body fat percentage were extracted from GWAS data as instrumental variables (IVs). Two-sample MR initially explored causal relationships between these factors and inguinal hernia risk. Multivariable Mendelian randomization (MVMR) assessed the direct causal effects of exposures on inguinal hernia. Positive findings from the MVMR analysis were independently validated. The inverse-variance weighted Methods (IVW), weighted median(WM), and MR-Egger were used for the MR estimates. Sensitivity analyses were used to examine the stability and reliability of the results. Two-sample MR analysis revealed a suggestive causal association between height and inguinal hernia (OR = 1.091, 95% CI = 1.003–1.186, P = 0.042). BMI (OR = 0.846, 95% CI = 0.774–0.924, P < 0.001) and body fat percentage (OR = 0.793, 95% CI = 0.690–0.911, P = 0.001) were significantly protective factors. After MVMR adjustment, BMI (OR = 0.746,95%CI = 0.638–0.872, P < 0.001) remained protective. Independent validation yielded consistent result. Genetically predicted BMI is a significant protective factor for inguinal hernia, providing valuable guidance for individualized prevention strategies.